2019
DOI: 10.1002/ppul.24287
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound for prediction of respiratory support in infants with acute bronchiolitis: A cohort study

Abstract: Objective Respiratory tract infections are among the most common causes of morbidity and mortality worldwide. Acute bronchiolitis (AB) is the leading cause of hospital admission among infants. Clinical scores have proven to be inaccurate in predicting prognosis. Our aim was to build a score based on findings of lung ultrasound (LU) performed at admission, to stratify patients at risk of needing respiratory support (non‐invasive and invasive ventilation). Study design Prospective, multicenter study including in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 27 publications
(53 reference statements)
10
57
0
Order By: Relevance
“…Currently, different LUS score protocols have been used to guide surfactant administration, respiratory support, and prognosis assessment . Our results suggest that the BLS is highly correlated with the PaO 2 /FiO 2 ratio, which is consistent with previous data revealing that the LUS score was significantly correlated with the oxygenation index in critical care patients .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Currently, different LUS score protocols have been used to guide surfactant administration, respiratory support, and prognosis assessment . Our results suggest that the BLS is highly correlated with the PaO 2 /FiO 2 ratio, which is consistent with previous data revealing that the LUS score was significantly correlated with the oxygenation index in critical care patients .…”
Section: Discussionsupporting
confidence: 91%
“…Currently, different LUS score protocols have been used to guide surfactant administration, respiratory support, and prognosis assessment. 11,16,38 Our results suggest that the BLS is highly correlated with the PaO 2 /FiO 2 ratio, which is consistent with previous data revealing that the LUS score was significantly correlated with the oxygenation index in critical care patients. 39 These findings are also consistent with those reported by Bilotta et al 40 When the BLS ranged from 49 to 64 (infusion volume, 6-8 mL/kg) in our study, the PaO 2 /FiO 2 ratio decreased sharply ( Figure 12) but declined slowly when the BLS was < 49; these findings are in line with those of the pig model of acute lung injury induced by oleic acid, suggesting that the BLS increases before the decrease in the PaO 2 /FiO 2 ratio.…”
Section: Evlw Measurements Determined By Transpulmonary Thermodilutionsupporting
confidence: 92%
“…The total LUS score was in the range of 0-50 points, resulting from the sum of the scores for each individual zone (five areas: anterior parasternal, anterior axillary, posterior axillary, posterior paravertebral, posterior linea scapularis). The authors concluded that their results were consistent with the ones of the aforementioned studies [8,12] regarding the correlation with the clinical severity scores, and they confirmed the presence of a higher percentage of pulmonary anomalies in the posterior paravertebral and subscapular area, probably due to gravity or to the obligate supine position of the child.…”
Section: Lus and Clinical Progression Of Bronchiolitissupporting
confidence: 80%
“…An additional prospective, multicenter research trial has demonstrated that LUS could be a helpful tool to identify patients at risk for any type of respiratory support (non-invasive or invasive ventilation, except conventional low-flow oxygen through nasal sprongs) in the acute phase of bronchiolitis, starting from the idea that clinical scores have proven to be inaccurate in predicting prognosis. In fact, Bueno-Campaña et al [12] have analyzed the data of 145 infants < 6 months with the aim to build a score based on LUS findings (presence and localization of B-lines, B-lines confluence and/or consolidation) performed at admission, but also on clinical data (age < or > 1 month and Wood-Downes-Ferres Score, typically used for asthma). Their results were consistent with the ones of the previously described studies, especially regarding the increased association of NIV with posterior consolidations > 1 cm.…”
Section: Lus and Clinical Progression Of Bronchiolitismentioning
confidence: 99%
See 1 more Smart Citation